2015
DOI: 10.1111/coa.12341
|View full text |Cite
|
Sign up to set email alerts
|

An evidence‐based approach to the management of snoring in adults

Abstract: A structured history of snoring and its associated symptoms, comprehensive examination including flexible laryngoscopy and sleep studies where relevant, in addition to targeted investigations, should lead to the correct diagnosis and appropriate management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Further studies using such methods are encouraged, to confirm the findings of the present study. Effective treatments are also available for snoring, such as low-level continuous positive airway pressure (CPAP), oropharyngeal exercises, oral appliance therapy, and the use of specific types of pillows [29][30][31][32][33] . A recent review indicated that CPAP, the first-line treatment for OSAS, may be beneficial with regard to liver disease in people with OSAS, independent of metabolic risk factors 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Further studies using such methods are encouraged, to confirm the findings of the present study. Effective treatments are also available for snoring, such as low-level continuous positive airway pressure (CPAP), oropharyngeal exercises, oral appliance therapy, and the use of specific types of pillows [29][30][31][32][33] . A recent review indicated that CPAP, the first-line treatment for OSAS, may be beneficial with regard to liver disease in people with OSAS, independent of metabolic risk factors 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, virtually all current treatments involve methods to open the airway. Life‐style modifications include weight loss, smoking cessation, limiting alcohol consumption, and improved sleep hygiene . Over‐the‐counter treatment options include nasal sprays, nasal strips or dilators, lubricating sprays, and “anti‐snore” clothing and pillows.…”
Section: Introductionmentioning
confidence: 99%
“…Life-style modifications include weight loss, smoking cessation, limiting alcohol consumption, and improved sleep hygiene. [10][11][12] Over-the-counter treatment options include nasal sprays, nasal strips or dilators, lubricating sprays, and "anti-snore" clothing and pillows. Surgical correction is usually reserved for patients with associated moderate to severe OSA.…”
mentioning
confidence: 99%
“…Obstructive sleep Apnea (OSA) is a sleep-related breathing disorder characterized by recurrent episodes of apnea and/or hypopnea, which leads to decreased oxygen saturation [1]. Snoring occurs because of a partially obstructed airway, typically due to the collapse and vibration of the pharyngeal tissues [2]; whereas, OSA occurs when there is no airflow despite a respiratory effort. Snoring and OSA can have adverse effects even on those other than the patients, such as impaired relationships with spouses or partners [3].…”
Section: Introductionmentioning
confidence: 99%